STRESS FIELDS AND GEOLOGICAL STRUCTURE OF WESTERN CLOSURE OF HORLIVKA ANTICLINE OF DONBAS. PART 1. STRUCTURAL PARAGENESIS - NIKITENKO, Oleksandr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on kinematic methods of studying fault and fracture structures in combination with traditional geological and structural methods, the structural and tectonophysical features and formation regularities of the geological structure of the western periclinal closure of the Horlivka anticline of the Donbas were studied. The kinematics, morphological features, and age relationships of tectonic faults in the study area were investigated. The structural paragenesis of the deformation elements of the rock massif was highlighted.
Keywords: geological structure; strike-slip faults; shear zone; slickenlines; structural paragenesis